Acupuncture and Related Therapies for Symptom Management in Palliative Cancer Care: Systematic Review and Meta-Analysis. Issue 9 (March 2016) - Lau, Charlotte H. Y.; Wu, Xinyin; Chung, Vincent C. H.; Liu, Xin; Hui, Edwin P.; Cramer, Holger; Lauche, Romy; Wong, Samuel Y. S.; Lau, Alexander Y. L.; Sit, Regina S. T.; Ziea, Eric T. C.; Ng, Bacon F. L.; et al.
Abstract : Abstract: Available systematic reviews showed uncertainty on the effectiveness of using acupuncture and related therapies for palliative cancer care. The aim of this systematic review and meta-analysis was to summarize current best evidence on acupuncture and related therapies for palliative cancer care. Five international and 3 Chinese databases were searched. Randomized controlled trials (RCTs) comparing acupuncture and related therapies with conventional or sham treatments were considered. Primary outcomes included fatigue, paresthesia and dysesthesias, chronic pain, anorexia, insomnia, limb edema, constipation, and health-related quality of life, of which effective conventional interventions are limited. Thirteen RCTs were included. Compared with conventional interventions, meta-analysis demonstrated that acupuncture and related therapies significantly reduced pain (2 studies, n = 175, pooled weighted mean difference: −0.76, 95% confidence interval: −0.14 to −0.39) among patients with liver or gastric cancer. Combined use of acupuncture and related therapies and Chinese herbal medicine improved quality of life in patients with gastrointestinal cancer (2 studies, n = 111, pooled standard mean difference: 0.75, 95% confidence interval: 0.36–1.13). Acupressure showed significant efficacy in reducing fatigue in lung cancer patients when compared with sham acupressure. Adverse events for acupuncture and related therapies were infrequent and mild. Acupuncture and related therapies are effective in reducing pain, fatigue, and in improving quality of life when compared with conventional intervention alone among cancer patients. Limitations on current evidence body imply that they should be used as a complement, rather than an alternative, to conventional care. Effectiveness of acupuncture and related therapies for managing anorexia, reducing constipation, paresthesia and dysesthesia, insomnia, and limb edema in cancer patients is uncertain, warranting future RCTs in these areas. Abstract : Supplemental Digital Content is available in the text